Carbon credit restoration projects in the Eastern Cape province of South Africa: considerations for sustainable local economic development - Polak, James Samuel (Rhodes University, Faculty of Commerce, Department of Economics and Economic History, 2017)
Although global climate change has been identified as a serious global economic, social, and environmental threat to society, national governments have been slow to respond on a global scale. Environmental economic theory offers market-based solutions to address climate change efficiently through carbon control regimes, such as carbon taxation and cap-and-trade policy. A major political milestone was reached when an international agreement entered into force in 2008, known the Kyoto Protocol, which incorporated a market-based solution to address climate change on a global scale. This allowed a global market for emissions to form through the Clean Development Mechanism. Although the Kyoto Protocol aimed to address a global issue on a global scale through a single global market for emissions, fragmented sovereign cap-and-trade schemes have since emerged in the form of national and regional emission markets, commonly referred to as carbon markets. The Clean Development Mechanism offered the opportunity to generate carbon credits through carbon offset projects, such as carbon restoration projects. Although the Kyoto Protocol did not achieve the objective of forming an internationally accepted global carbon control regime, it seems to have set a trend of including offset programs in newly emerging carbon control regimes, such as South Africa's proposed carbon tax. This study set out to assess the extent to which carbon control regimes are enabling sustainable local economic development, based on carbon restoration projects in the Eastern Cape province of South Africa using Portulacaria afra, commonly known as spekboom. As a starting point, this study assessed the current state of the international carbon markets using significant international cap-and-trade based markets as examples. Based on Newell et al.'s (2013) selection of significant carbon markets and data availability, the United States' Regional Greenhouse Gas Initiative and the European Union's Emission Trading Scheme were selected. Historical, current and forecasted supply and demand data were gathered from Thomson Reuters' Point Carbon research division. Further, historical futures and spot market price and volume data were gathered from the markets to compare how prices have fared over time. The Clean Development Mechanism's market for Certified Emission Reduction credits was used for comparative purposes. The markets were found to be systemically oversupplied, leading to systemically low prices. The systemic oversupply in credits provides a limited incentive to initiate carbon offset projects, however, South Africa's proposed carbon tax may be able to stimulate demand for domestic offset projects. Key success factors established through a comparative literature review on local economic development theory were incorporated into key informant interviews. The results were then analysed through the lens of Connelly's (2007) model for sustainable development to provide recommendations for sustainable local economic development, regarding carbon restoration projects in the Eastern Cape using P. afra. The following opportunities were identified: the planting of P. afra on degraded land has the potential to mitigate climate change, offer water benefits to the surrounding communities, and promote biodiversity regeneration. There is potential for economic growth through job creation and the economic multiplier effect. Government funding is available and voluntary offset agreements do exist, eliminating a large portion of the cumbersome accreditation requirements. These projects also offer potential for social justice through the government funding requirements which stipulate that youth and women should be given preference for employment, potentially helping to alleviate inequality. The funding further stipulates that employees should be trained in transferable skills, offering potential for capacity building and social capital accumulation through education. These transferable skills include skills geared towards encouraging entrepreneurialism. Corresponding challenges were also found: excessive overgrazing through pastoralism has rendered some land degraded beyond restoration. Opportunists may resort to planting P. afra outside of the subtropical Albany Thicket biome to which it is endemic, leading to potential biodiversity loss rather than gains. Sufficient buy-in is required from private landowners for these projects to be sustainable, however, the projects entail a large opportunity cost to farmers as returns take at least 5 to 6 years. This may render these projects undesirable to most landowners and provides scope for free-riding, should pastoralists not have to bear the full costs of the project and property rights not be enforced through land user agreements. The projects require an exorbitant amount of upfront funding. Cash flow received from the projects does not extend in perpetuity. Requirements for social justice pertain only to government funded projects. A working model, generating and selling carbon credits through land restoration using P. afra, has not yet been established. As it stands, these carbon restoration projects are still highly speculative and carry a significant amount of investment risk, given the high mortality and low growth rates associated with the current planting method. The current systemic oversupply of carbon. credits in the international markets signal that returns from carbon credits are set to be low, at least until the oversupply issues are resolved. Should these challenges be overcome, carbon restoration projects using P. afra may have the potential to bolster sustainable local economic development in the impoverished regions of province as well as provide a locally-driven adaptation and mitigation strategy to address global climate change.
Keywords: Uncatalogued